Trust in work teams: An integrative review, multilevel model, and future directions. (7th July 2017) - Costa, Ana Cristina; Fulmer, C. Ashley; Anderson, Neil R.
Summary: This article presents an integrative review of the rapidly growing body of research on trust in work teams. We start by analyzing prominent definitions of trust and their theoretical foundations, followed by different conceptualizations of trust in teams emphasizing its multilevel, dynamic, and emergent nature. We then review the empirical research and its underlying theoretical perspectives concerning the emergence and development of trust in teams. On the basis of this review, we propose an integrated conceptual framework that organizes the field and can advance knowledge of the multilevel nature of trust in teams. Our conclusion is that trust in teams resides at multiple levels of analysis simultaneously, is subject to factors across levels in organizations, and impacts performance and other relevant outcomes both at the individual and team levels. We argue that research should not only differentiate between interpersonal trust between members from collective trust at the team level but also emphasize the interplay within and between these levels by considering cross‐level influences and dynamics. We conclude by proposing 4 major directions for future research and 3 critical methodological recommendations for study designs derived from our review and framework.